Preventing Domestic Violence Early: Legal Education for Generation Z at Ponpes Terpadu Daarul Amanah An Nahdhiyah - Bustomi; Mohamad Mahrusillah (International Research and Development for Human Beings (IRDH), 2025)
Tangerang City, as a multicultural urban area, faces various social challenges, including domestic violence (DV), which has serious impacts on victims and the social environment. Generation Z, as a productive age group still developing their character, has great potential as agents of domestic violence prevention if equipped with the right legal understanding. This article discusses the results of community service activities aimed at improving legal literacy regarding criminal sanctions for domestic violence among Gen Z students through interactive seminars. The activities were carried out in several high schools and vocational schools in Tangerang City and included legal material presentations, case study discussions, and role-playing simulations. The results of the activities showed a significant increase in students' understanding of Law Number 23 of 2004 concerning the Elimination of Domestic Violence, the types of violence regulated, and the criminal consequences for perpetrators. Participants demonstrated positive responses through active participation, courage to ask questions, and the ability to re-explain the material. In addition, students took the initiative to form